The effects of short term detraining and retraining on physical fitness in elite soccer players - Joo, C. H. (PLOS ONE, 2018)
The aim of this study was to examine the effects of aerobic high-intensity training with reduced volume and training cessation on body composition and physical fitness after the end of season and the time required to recapture physical fitness with intensified retraining following two weeks of detraining in elite soccer players. Method: Twenty male semi-professional soccer players participated in this study. The soccer players were assigned to either a group that completed high-intensity aerobic training (HAT, n = 10) or to a detraining and retraining group (DHAT, n = 10) for a 5-week period immediately after the end of the season. The first 2 weeks of the period, members of the HAT group performed high-intensity aerobic exercise (80-90% of HRmax, 12 min × 3, three times per week), whereas members of the DHAT group abstained from any physical activity. During the subsequent 3 weeks, members of both the HAT and DHAT groups completed high-intensity aerobic exercise. Exercise performance testing and body composition analysis were performed before; after 2 weeks of detraining; and at 1, 2 and 3 weeks of retraining. Results: Intensified high-intensity training for 5 weeks maintained the performance in the Yo-Yo Intermittent Recovery level 2 test (Yo-Yo IR2) and repeated sprints at any time point (P > 0.05). However 2 weeks of detraining resulted in significant decreases in the performance on the Yo-Yo IR2 (P < 0.01) and repeated sprints test (P < 0.05). Performance on the Yo-Yo IR2 enhanced after 2 weeks of retraining and was maintained up to 3 weeks after retraining, with no significant differences between conditions (P > 0.05). In addition, repeated sprint performance markedly decreased after the detraining period (P < 0.05) and was continuously lower compared to the baseline at 2 weeks after retraining (P < 0.05). Furthermore, this value reached baseline level at the end of the experimental period (P > 0.05). There were no significant differences between conditions in body composition, performance of agility, or sprint ability throughout the 5-week experimental period (P > 0.05). Conclusions: The present data suggest that short-term detraining after the competitive season can markedly decrease performances in the Yo-Yo IR2 test and repeated sprints. To return to a previous level of ability on the Yo-Yo IR2 and/or sprint test with retraining through high-intensity aerobic training after a period of detraining, a similar or longer period of retraining is required. However, the high-intensity training with reduced amount of training after competitive season can prevent reductions in physical fitness.